A review on treatment techniques to improve the durability of recycled aggregate concrete: Enhancement mechanisms, performance and cost analysis. (1st September 2022) - Bahraq, Ashraf A.; Jose, Jobin; Shameem, Mohammed; Maslehuddin, Mohammed
Abstract: It is well-recognized that recycled aggregate (RA), obtained from dismantled structures, is more porous and less dense, than natural aggregate (NA) due to the presence of adhering cement mortar. Thus, the durability of concrete manufactured with RA, called recycled aggregate concrete (RAC), is inferior to that of natural aggregate concrete (NAC), thus limiting the use of the former on an industrial scale. This paper provides a state-of-the-art review on the durability properties, such as permeability, carbonation, reinforcement corrosion and shrinkage of RAC. The effect of factors influencing the durability of RAC are also discussed. Additionally, the treatment methods that can be used to improve the durability of RAC are critically reviewed, and possible mechanisms of improvement are highlighted. In addition, a comprehensive analysis of the cost of treating RA is carried out. Lastly, recommendations on future research are made. This review would be useful for researchers and engineers to select the optimal treatment schemes for improving the quality of RA and, consequently, the durability of RAC. Graphical abstract: Image 1 Highlights: Recycled aggregate (RA) needs to be treated to improve the durability of RAC. A state-of-the art review on durability of RAC and treatment methods is presented. Cost analysis of treating RA and recommendations for future research are provided. This review will be useful in selecting methods for improving the durability of RAC.